The Effect of Profit Sharing Ratio And Corporate Social Responbility on Financial Performance of Sharia Commercial Banks With Intelectual Capital As A Moderating Variable - Putri Amanatus Stalistah; Fadlil Abdani (JURNAL PENELITIAN EKONOMI DAN AKUNTANSI (JPENSI), 2022)
This study aimed to determine how profit sharing ratios and corporate social responsibility affect the financial performance of Islamic commercial banks with intellectual capital as a moderating variable. This research was conducted on Indonesian Islamic commercial banks registered with OJK from 2018-2020. The number of samples used as many as 14 samples with purposive sampling method. The analysis technique used is multiple linear regression analysis. Based on the results of the analysis, it was found that the profit sharing ratio and corporate social responsibility had no effect on financial performance. Intellectual capital is not able to moderate the profit sharing ratio on financial performance. Intellectual capital is not able to moderate corporate social responsibility on financial performance.